2020
DOI: 10.1021/jacs.0c07390
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Halistatins 1 and 2

Abstract: The first total synthesis of halistatins 1 and 2 has been completed using Cr-mediated coupling reactions for the C11/C12, C17/C18, and C19/C20 bond formation. For the C11/C12 bond formation, a stoichiometric Ni/Cr-mediated reaction is used to couple an α-quaternary aldehyde with a vinyl iodide. The solubilized Cr-reagent, prepared from CrCl2 and a sulfonamide ligand, allows one to perform the coupling with ∼1 equiv of Cr-reagent. Catalytic, asymmetric Co/Cr-mediated iodoallylation is adopted to incorporate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…483 The rst total synthesis of the structure reported for halisphingosine A has called into question the congurational assignment of the NP. 484 Other rst total syntheses include that of an acetylene, 485 two peptides, 486,487 and two macrolides, 488,489 the latter describing the construction of the highly complex halistatins 1 and 2. The synthesis of the proposed structure of poly-cationic alkaloid protoaculeine B has been achieved, although the spectroscopic data of the natural and synthetic material differ, suggesting revision is necessary.…”
Section: Reviewmentioning
confidence: 99%
“…483 The rst total synthesis of the structure reported for halisphingosine A has called into question the congurational assignment of the NP. 484 Other rst total syntheses include that of an acetylene, 485 two peptides, 486,487 and two macrolides, 488,489 the latter describing the construction of the highly complex halistatins 1 and 2. The synthesis of the proposed structure of poly-cationic alkaloid protoaculeine B has been achieved, although the spectroscopic data of the natural and synthetic material differ, suggesting revision is necessary.…”
Section: Reviewmentioning
confidence: 99%
“…The halichondrin family of natural products constitutes a group of challenging and inspiring molecules to synthetic and medicinal chemists due to their complex molecular structures and their potent antitumor properties. From this class (e.g., 1 – 5 , Figure ), halichondrin B ( 1 ) and norhalichondrin B ( 2 ) represent the two most pursued members due to their early isolation, rarity, and potent biological activities .…”
Section: Introductionmentioning
confidence: 69%
“…An elegant work by Kishi and co-workers demonstrated that a higher coupling efficiency could be achieved with a 1:1 molar ratio of coupling partners using the NI/Zr-mediated one-pot ketone synthesis . The experimental simplicity of their method was perfectly applied to the late-stage couplings of halichondrins …”
mentioning
confidence: 99%
“…Inspired by recent efforts by the Kishi group, we sought to employ thiopyridine esters as suitable coupling partners in direct ketone synthesis because of their ease of handling and storage. , Furthermore, the direct coupling of thiopyridine esters with primary alkylpyridinium salts has not been optimized yet.…”
mentioning
confidence: 99%